35kV chain-type H-bridge cascaded DC voltage control method - DUAN MEIZHU; LI GUANGRUI; GU JINMAO; LI XIAOLIANG; ZHU GUITANG; CAO XIAOLIANG; MAO XIANYE (2017)
The invention discloses a 35kV chain-type H-bridge cascaded DC voltage control method and belongs to the power electronics field and the power system field, and solves a problem of stable operation of a power unit in 35kV chain-type SVG control. According to the invention, in consideration of power grid voltage imbalance, power unit electric parameter difference and the like, three-layer control over H-bridge DC voltage is performed. The first layer control is all power unit H-bridge total DC voltage control. The second layer control is inter-phase DC voltage control. The third layer control is power unit DC voltage balance. Therefore, independent adjustment of active components of each unit individuals is realized, so that DC voltage balance between units is controlled and a problem of inter-phase imbalance is solved effectively. 本发明公开了种35kV链式H桥级联直压的控制方法，属于电力电子领域和电力系统领域，家觉在35kV链式SVG控制中，功率单元的稳定运行问题，该方法在考虑电网电压不平衡、功率单元电气参数差异等条件下，对H桥直压进行三层控制。第层控制为所有功率单元H桥总直压控制，第二层控制为相间直压控制，第三层控制为功率单元直压均衡，可实现对单个单元有功分量的独立调节，从而控制单元